Housing Trajectories of Forensic Psychiatric Patients. (3rd May 2016) - Salem, Leila; Crocker, Anne G.; Charette, Yanick; Earls, Christopher M.; Nicholls, Tonia L.; Seto, Michael C.
Abstract : The objectives of this study were to describe the disposition and housing trajectories of individuals found Not Criminally Responsible on account of Mental Disorder (NCRMD), and the factors that predict different trajectories. To do so, disposition and housing status were coded for 934 NCRMD patients over a 36‐month follow‐up period. Sequential data analysis resulted in four distinct trajectories: detention in hospital, conditional discharge in supportive housing, conditional discharge in independent housing, and absolute discharge to unknown housing. The likelihood of a placement in supportive housing compared with detention significantly decreased for individuals with a higher index offense severity. Less restrictive trajectories were significantly predicted by clinical factors. The results revealed little change in the disposition and housing trajectories of NCRMD patients. Furthermore, decisions about disposition and housing placement reflect a knowledge–practice gap between risk factors known to be predictive of community resources use in the forensic population. Copyright © 2016 John Wiley & Sons, Ltd.